Aprendizagem significativa nas aulas de leitura: uma proposta da escola - Lopes, Reginaldo Silva (2008)
This paper has aimed at proposing a distinguished strategy for Reading Classes at a state-owned school in São Paulo, founded on David Ausubel's meaningful learning theory. This work has provided different and focused activities with various texts at the school´s library, by using previous organizers and the work with diverse references and considering the pupil´s personal and individualized cognitive structure, besides the whole organized content of an individual idea. It has established the Reading Diary as a means to register reading texts and dialogues between the pupil and the writer, the pupil and the teacher and the pupil and the pupil. It has taken into account the pupil's previous knowledge of a specific matter or theme in order to establish a new learning and incorporate it in the pupil's cognitive structure. During the process, the new dynamic initiated in Reading Classes has been incorporated in Portuguese classes, evidencing that one may enlarge the horizon of a specific work methodology when the pupil is viewed as a fundamental element in the learning process and its abilities and knowledge are respected and appreciated, like its participation in the classes. The results have showed that the pupils have developed potentialities for reading, interpreting and creating texts with meaningful qualitative gains, not only in Portuguese but in other subjects as well. The study also shows that it is possible to seek alternatives, though limited to the reality of public schools, which favors the pupil's learning and development